Subjective Theories of Chinese Office Workers With Irregular Physical Activity: An Interview-Based Study - Shang, Borui; Duan, Yanping; Brehm, Walter; Liang, Wei (Frontiers in Psychology, 2022)
Objectives Individuals with irregular physical activity (PA) participation are defined as fluctuators. This study aimed to comprehend how fluctuators’ perceived barriers and motivators in their subjective theories are exhibited and cognitively represented in relation to their everyday PA practices and lapses. Methods The design of “Research Program Subjective Theories” was used to explore and present fluctuators’ cognition concerning PA participation. Thirty fluctuators were invited to a semi-structured interview. By inductive and deductive coding, fluctuators’ verbal data were converted into word categories for extracting commonalities and comparing differences. By retaining the remaining word categories of high frequency and exploring the interrelationships among the remained word categories using statistical analyses, a superstructure (i.e., visualized representation of fluctuators’ overall cognition) including fluctuators’ main PA motivators, barriers, and behavioral outcomes was compiled. Results Fluctuators face common motivators as barriers, such as lack of time, lack of willpower, lack of social support, and physical reasons (discomfort, injuries, or diseases). Fluctuators’ subjective theories primarily differed in motivational configurations. The physically motivated fluctuators (i.e., those predominantly motivated by physically related motivators) were more linked with low PA level, while the mixed motivated fluctuators (i.e., motivated by both physically related and emotionally or socially related motivators) were more likely associated with moderate PA level. The exemplars of the three typical fluctuators were also demonstrated to reveal their real experiences and situations in the daily life context. Conclusion Due to the fact that fluctuation research is still in its infancy, this study represents a significant opportunity to promote knowledge growth in this area. Future studies are recommended to convert findings of the present study into interventions that benefit fluctuators in overcoming perceived barriers and enhancing motivations to eventually participate in regular PA.